Isolation, characterization and chromosome localization of repetitive DNA sequences in bananas (Musa spp.) - Valárik, M; Simková, H; Hribová, E; Safár, J; Dolezelová, M; Dolezel, J (Chromosome research, 2002)
Partial genomic DNA libraries were constructed in Musa acuminata and M. balbisiana and screened for clones carrying repeated sequences, and sequences carrying rDNA. Isolated clones were characterized in terms of copy number, genomic distribution in M. acuminata and M. balbisiana, and sequence similarity to known DNA sequences. Ribosomal RNA genes have been the most abundant sequences recovered. FISH with probes for DNA clones Radkal and Radka7, which carry different fragments of Musa 26S rDNA, and Radka14, for which no homology with known DNA sequences has been found, resulted in clear signals at secondary constrictions. Only one clone carrying 5S rDNA, named Radka2, has been recovered. All remaining DNA clones exhibited more or less pronounced clustering at centromeric regions. The study revealed small differences in genomic distribution of repetitive DNA sequences between M. acuminata and M. balbisiana, the only exception being the 5S rDNA where the two Musa clones under study differed in the number of sites. All repetitive sequences were more abundant in M. acuminata whose genome is about 12% larger than that of M. balbisiana. While, for some sequences, the differences in copy number between the species were relatively small, for some of them, e.g. Radka5, the difference was almost thirty-fold. These observations suggest that repetitive DNA sequences contribute to the difference in genome size between both species, albeit to different extents. Isolation and characterization of new repetitive DNA sequences improves the knowledge of long-range organization of chromosomes in
Keywords: Sequence Analysis, DNA; Musa; DNA rostlinná; repetitivní sekvence nukleových kyselin; ribozomální DNA; sekvenční analýza DNA; In Situ Hybridization, Fluorescence; DNA, Plant; Karyotyping; Chromosome Mapping; DNA, Ribosomal; Repetitive Sequences, Nucleic Acid; banánovník; karyotypizace; mapování chromozomů; hybridizace in situ fluorescenční; chromozomy rostlin; Chromosomes, Plant